O império das repúblicas: projetos políticos republicanos no Espírito Santo, 1870-1908 - Siqueira, Karulliny Silverol (2016)
Starting from 1870, with the actions of radical liberals, and later with the creation of the Republican Party in the Court, the criticism of the Brazilian Empire was intensified. In the perception of such group, the Republic became the only solution to the country's problems. Republican ideas, however, were not homogeneous in the Empire, since at least three Republicans models have been experimented in the last years of the nineteenth century: the Jacobin project, supported by the French slope, the positivist republican project, and even the American liberal project. Thus, by identifying the plurality of the republicanism nationwide, this study aims to understand the Republican projects that competed for space in Espírito Santo in the last years of the nineteenth century, also highlighting the process of consolidation of the new regime. The present study intends to, in this sense, identify the reception of the republican currents emanating from the Court, in order to understand the reframing of these ideals in the face of local demands. This research has the press as the main documentary corpus, identifying it as a space conducive to political debate of the period and also as a party vehicle of local political groups. For the analysis of documentation, this research is based on the study of political languages, proposing the identification of the words most used among the Republican propaganda in the Espírito Santo, in order to understand the different political projects in discussion, in addition to the composition of a new language, also permeated by resignifications that made up the politic dynamics of the new regime. In addition to the study of languages, this research is also guided by the concept of political culture, in order to identify the new values and symbols which were inserted into the capixaba society after the advent of the Republic. Based on the abovementioned theoretical and methodological assumptions, it is possible to highlight the specifics of the republicanism in the Espírito Santo, delimiting its temporalities, and its distinctive characteristics in different parts of the province, which in turn will conflict until mid-1908, moment of consolidation of the local Republican politics